2014
DOI: 10.1007/s00423-014-1241-3
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of liver resection for non-colorectal, non-neuroendocrine liver metastases: a systematic review

Abstract: There appears to be a benefit to resection for patients with NCRNNE liver metastases. The degree of survival advantage is predicated by primary site.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 91 publications
(72 reference statements)
3
37
0
Order By: Relevance
“…Factors in the score include: patient age at operation, primary tumor site and histology, disease‐free interval before resection, presence of extrahepatic metastases at time of operation, extent of resection and margin of resection . In the original AFC development cohort, a low score (0 to 3) led to a 5‐year survival of 46% (range, 36% to 69%), while an intermediate score had a survival of 33% (range, 5%–46%), and a high‐risk score (>6) had a 5‐year survival of only 2% (range, 0% to 11%). Patients in the external validation cohort were grouped in three risk categories according to the AFC scores as listed above…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Factors in the score include: patient age at operation, primary tumor site and histology, disease‐free interval before resection, presence of extrahepatic metastases at time of operation, extent of resection and margin of resection . In the original AFC development cohort, a low score (0 to 3) led to a 5‐year survival of 46% (range, 36% to 69%), while an intermediate score had a survival of 33% (range, 5%–46%), and a high‐risk score (>6) had a 5‐year survival of only 2% (range, 0% to 11%). Patients in the external validation cohort were grouped in three risk categories according to the AFC scores as listed above…”
Section: Methodsmentioning
confidence: 99%
“…However, the benefit of surgical treatment of noncolorectal, nonneuroendocrine liver metastases (NCNNELM) remains poorly defined and debated . Numerous studies and subsequent meta‐analyses have been published looking at liver resection (LR) for site‐specific NCNNELM . Limitations from these studies hampers the robustness and generalizability of the results as evidenced by inconsistent results, heterogeneous populations, and large confidence intervals (CIs) when attempting to pool data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a recent review about non-colorectal non-neuroendocrine liver metastases demonstrated surgery to be a benefit for these kinds of metastatic patients, especially for those affected by primary testicular, ovarian, and renal cell cancers but also for women with isolated breast cancer metastases to the liver [10].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the reports refer to smaller, retrospective case series with poorly defined inclusion criteria, heterogeneous patient cohorts and tumour stages, scarce information on treatment carried out during the patient journey, and poor quality of treatment outcome reporting. In two recent systematic reviews on liver resection for non-colorectal, non-neuroendocrine liver metastases and Yttrium-90 selective internal radiation therapy (SIRT) in the same patient population, respectively, the primary tumour site was identified as the most important predictor of outcome [3,4]. Patients with liver metastases from testicular, ovarian, and renal cell carcinoma, sarcoma, or those with isolated hepatic metastases of breast cancer seem to experience a survival benefit Published online: December 9, 2015…”
mentioning
confidence: 99%